In vivo imaging of the inner retinal layer structure in mice after eye-opening using visible-light optical coherence tomography. (October 2021) - Beckmann, Lisa; Cai, Zhen; Cole, James; Miller, David A.; Liu, Mingna; Grannonico, Marta; Zhang, Xian; Ryu, Hyun Jung; Netland, Peter A.; Liu, Xiaorong; Zhang, Hao F.
Abstract: The growth of the mouse eye and retina after birth is a dynamic, highly regulated process. In this study, we applied visible-light optical coherence tomography (vis-OCT), a non-invasive imaging technique, to examine developing retinal layer structures after eye-opening. We introduced a resampled circumpapillary B-scan averaging technique to improve the inter-layer contrast, enabling retinal layer thickness measurements as early as postnatal day 13 (P13) – right after eye-opening. We confirmed vis-OCT measurements using ex vivo confocal microscopy of retinal sections at different ages. Our results demonstrate that vis-OCT can visualize the developmental murine retinal layer structure in vivo, which offers us new opportunities to better characterize the pathological alterations in mouse models of developmental eye diseases. Highlights: Visible-light OCT can visualize the retinal layer structure as early as the time of eye-opening. In vivo visible-light OCT measurements are validated by ex vivo confocal microscopy. Individual inner retinal layers develop and refine differently with age.